1963
DOI: 10.1177/004051756303300611
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Thermal Analysis of Natural and Modified Wool and Mohair

Abstract: JUNE 1963 .oj~l.l I 465 set. Thus, except in the case of the T -set condition, the fibers were exposed to water at 97°C for 4 hr, and therefore the differences in fiber structure of the p-set and P-T-set fibers must be due to the mechanical restraint conditions imposed during the treatments. The fact that the P-T fibers are stronger and less extensible than the corresponding P-set fibers suggests a more perfect network of secondary and primary bonding in the P-T condition. It would also suggest that relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
3

Year Published

1971
1971
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(16 citation statements)
references
References 7 publications
4
9
0
3
Order By: Relevance
“…In the DSC curves of cr-keratins, one or two endothermic peaks are observed in the temperature range 230 ~ ~ (see Fig. 2) which have been interpreted contradictorily in terms of helix melting points [3][4][5] (i. e. microfibrillar origin) and cystine decomposition points [6][7][8][9] (i. e. matrix origin). DSC investigations of isolated microfibrillar and matrix proteins in the disulphide form have shown that the two endothermic peaks have a different origin: the first peak (lower temperature) is a microfibrillar peak and the second peak, a matrix peak [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the DSC curves of cr-keratins, one or two endothermic peaks are observed in the temperature range 230 ~ ~ (see Fig. 2) which have been interpreted contradictorily in terms of helix melting points [3][4][5] (i. e. microfibrillar origin) and cystine decomposition points [6][7][8][9] (i. e. matrix origin). DSC investigations of isolated microfibrillar and matrix proteins in the disulphide form have shown that the two endothermic peaks have a different origin: the first peak (lower temperature) is a microfibrillar peak and the second peak, a matrix peak [10].…”
Section: Introductionmentioning
confidence: 99%
“…6 The elimination of such simple molecules should be diminished by the grafting of MMA on the reactive sites, and this should increase the decomposition temperature of grafted wool compared to the natural sample. Chemical modification of wool which involves tlhe breakage of hydrogen bonding (formic acid treatment), formation of lanthionine, or reduction should also affect the decomposition temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Die Mikrofibrillen bestehen aus teilhelikalen, schwefelarmen (LS = Low-sulfur) Proteinen und sind in einer nichthelikalen, schwefelreichen (HS = High-sulfur) Matrix eingelagert. In den Thermogrammen von a-Keratinen beobachtet man im Temperaturbereich yon 230 bis 250 ~ einen bis zwei endotherme Peaks, die sowohl ais Helixschmelzpunkte [1][2][3] als auch als Cystinzersetzungspunkte [4][5][6][7] gedeutet worden sind. Deshalb schien es angebracht, die entsprechenden thermoanalytischen Untersuchungen an isolierten Mikrofibrillen-und Matrixproteinen durchzufiihren.…”
unclassified